Notes, new records, and transference in South American Cerambycidae (Insecta, Coleoptera) - Olivier, Renan Da Silva; Santos-Silva, Antonio; Monné, Marcela Laura; Costa-Pinto, Paula Jéssica (Zootaxa, 2024)
In this work we report for the first time the presence of 59 species of Cerambycidae (4 species of Prioninae, 25 species of Cerambycinae, and 30 species of Lamiinae) in Mato Grosso do Sul. One of these species, Ozodes infuscatus Bates, 1870, is also recorded from the Brazilian states of São Paulo. Nealcidion bruchi (Melzer, 1934) and Glypthaga arena Galileo, Martins & Santos-Silva, 2015 are recorded from Brazil for the first time. Lissonotus biguttatus Dalman, 1817 is newly recorded from Mato Grosso State. The type locality of Nesozineus lineolatus Galileo & Martins, 1996 is corrected, as well as state of the type locality of Oncideres malleri Fragoso, 1970, Aegomorphus lanei (Marinoni & Martins, 1978), and Carphina melanura Monné & Monné, 2007. Hovorodon Santos-Silva, Swift & Nearns, 2010 is confirmed as being masculine gender. The grammatical gender of Diploschema Thomson, 1858 is reported as neuter gender, and the names of D. maculata Martins & Monné, 1980 and D. brunnea Martins & Monné, 1980 are corrected. Canarana brachialis (Guérin-Méneville, 1855) is indicated as recorded from the Brazilian state of Mato Grosso do Sul and not Mato Grosso. Urgleptes melzeri (Gilmour, 1959) is reinstated to its original genus: Lepturges (Lepturges). Notes on nearly all species are provided, including number of specimens in the original description, type locality, dates, etc.